1998
DOI: 10.1346/ccmn.1998.0460403
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Mobility of Major and Trace Elements During Alteration of an Andesite and a Rhyolite to Bentonite, in the Islands of Milos and Kimolos, Aegean, Greece

Abstract: Abstract--Progressive alteration by seawater of an andesite in the Aegean Island of Milos and an ignimbrite in the Aegean Island of Kimolos, Greece, formed bentonites with or without zeolites. Both profiles are dominated by migration of alkalis and uptake of Mg, Fe and H20, while A1 and Ti are immobile. The relative removal of alkalis controls the formation of either smectite or zeolites. The behavior of Ca and Si depends on the chemistry of the parent rock. In the rhyolitic profile, alteration is controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 55 publications
4
89
0
11
Order By: Relevance
“…How ever, there are many re ports that trace el e ments are mo bi lised dur ing al ter ation pro cesses (e.g., Winchester and Floyd, 1977b;Zielinski, 1982;Summa and Verosub, 1992;van der Weijden and van der Weijden, 1995;Christidis, 1998;Malpas et al, 2001;Büchl and Gier, 2003), though, as was reported by van der Weijden and van der Weijden (1995) the changes in REE val ues are not con sid ered to be sig nif i cant. More over, the au thors re ferred em pha sized that the mo bil ity of el e ments dur ing al ter ation pro cesses is ex tremely com plex and con trolled by sev eral fac tors.…”
Section: Fig 7 Rep Re Sen Ta Tive Xrd Pat Terns Of the >2 µM Frac Tmentioning
confidence: 92%
“…How ever, there are many re ports that trace el e ments are mo bi lised dur ing al ter ation pro cesses (e.g., Winchester and Floyd, 1977b;Zielinski, 1982;Summa and Verosub, 1992;van der Weijden and van der Weijden, 1995;Christidis, 1998;Malpas et al, 2001;Büchl and Gier, 2003), though, as was reported by van der Weijden and van der Weijden (1995) the changes in REE val ues are not con sid ered to be sig nif i cant. More over, the au thors re ferred em pha sized that the mo bil ity of el e ments dur ing al ter ation pro cesses is ex tremely com plex and con trolled by sev eral fac tors.…”
Section: Fig 7 Rep Re Sen Ta Tive Xrd Pat Terns Of the >2 µM Frac Tmentioning
confidence: 92%
“…Christidis (1998) showed that these chemical exchanges depend on the composition of the volcanic debris and the water/rock ratio in a marine system. Consequently, it is excluded to use the proportions of the major elements to determine the original glass composition.…”
Section: The Origin Of the Volcanic Glassmentioning
confidence: 99%
“…Riyolitik camın bentonite dönüşümünde Cs, Rb, U ve Zr alterasyonun ilk evrelerinde kayba uğrar, Sr, Sc, Cr ve Co farklı yollarla bentonitte zenginleşir [16] [18]. İncelenen örneklerdeki küçük Zr zenginleşmeleri bentonitleşme sırasında erimeyen kalıntı mineral (biyotit) yoluyla ve Zn zenginleşmeleri ise yapısal birleşme yoluyla (dış kaynaklı) gerçekleşmiş olmalıdır.…”
Section: Eser Elementlerunclassified
“…Sıcaklığın yüksek olduğu alterasyon şartlarında altere üründe Eu +2 zenginleşmesi meydana gelebilir [20,21]. Benzer olarak andezitik volkaniklerin bentonite dönüşümü sırasında ilerleyen alterasyona bağlı olarak plajiyoklasların smektite replase olması ile altere üründe Eu zenginleşir [18][19][20][21][22] [4], CaO zenginleşmesinin iyon değişimi yoluyla gerçekleştiğine işaret eder [27,28]. Zenginleşen Ca'un bir kısmı değişebilir katyon olarak montmorillonit yapısında tutulmuş geriye kalan Ca, bentonitler içinde gözlenen kalsit oluşumunda kullanılmıştır.…”
Section: Nadir Toprak Elementleriunclassified
See 1 more Smart Citation